Pelaksanaan The Sino-British Joint Declaration 1984 oleh Otoritas RRT Mengenai Pemberian Hak-Hak Otonomi bagi Wilayah Hong Kong - Ken Bagus Setya Dharma (Jurist-Diction, 2021)
AbstractHong Kong, a special autonomous region within the PRC's constitutional hierarchy, has a long history behind its privileges. It started with the defeat of the Qing Dynasty in a series of Opium Wars which ended with the 156-year rule of Hong Kong by the British which ended in 1997. However, the handover did not come easily. Based on The Sino-British Joint Declaration 1984, an international agreement made by Britain and China regarding the re-acceptance of Hong Kong, it promised Hong Kong to be an autonomous region for 50 years post-1997 except in the field of defence and cooperation with foreign powers. This article seeks to examine the implementation of The Sino-British Joint Declaration 1984 with a literature review method based on the rights it gives to the people of Hong Kong and the reality in daily life. Keywords: Implementation; The Sino-British Joint Declaration 1984; Hong Kong; Autonomy; International Agreement.AbstrakHong Kong yang merupakan sebuah wilayah otonomi khusus dalam hierarki ketatanegaraan RRT memiliki sejarah yang panjang yang melatarbelakangi keistimewaannya. Dimulai dari kekalahan Dinasti Qing dalam rentetan Perang Candu yang berakhir dengan penguasaan Hong Kong oleh Inggris selama 156 tahun yang berakhir pada 1997. Akan tetapi, penyerahan tersebut tidak terjadi dengan mudah. Berdasarkan The Sino-British Joint Declaration 1984, sebuah perjanjian internasional yang dibuat oleh Inggris dan RRT mengenai penerimaan kembali Hong Kong, ia memperjanjikan Hong Kong menjadi wilayah otonom selama 50 tahun pasca-1997 kecuali pada bidang pertahanan dan kerja sama dengan kekuatan asing. Artikel ini berusaha mengkaji penerapan The Sino-British Joint Declaration 1984 dengan metode kajian kepustakaan berdasarkan hak-hak yang diberikannya kepada rakyat Hong Kong dan kenyataannya dalam kehidupan sehari-hari.Kata Kunci: Pelaksanaan; The Sino-British Joint Declaration 1984; Hong Kong; Otonomi; Perjanjian Internasional.